Anxiety Disorder on The Main Character of A. J. Finn Novel The Woman in The Window - Eniwaty Silalahi; Amrin Saragih (Universitas Negeri Medan, 2021)
Principally, this research attempts to analyze the anxiety disorder on the main character of novel TheWoman In The Window by A. J. Finn. The objective of this study to find out 1) To investigate the causes ofanxiety disorder through to the main character in the novel based on the psychoanalytic approach bySigmund Freud. 2) To explain how the treatmentsdone by the main character to reduce her anxietydisorder in the novel and 3) To explain the reasons for the treatmentsdone by the main character in thenovel. The writer used qualitative design method in analyzing the data that focused on the textual data. Theinstruments for collecting data are readingtechnique, and writing technique. This research analyzesbyrelating the data with Freud’sPsychoanalysis theory. The results of theresearch show that 1) The causesanxiety disorder to the main character because have an accident in the past that make the sufferer becomestress, and post-traumatic stress disorder. 2) There are two treatments done by the main character toreduce her anxiety disorder that is medication and therapy. 3) The reasons for the treatments done by maincharacter because with healing through therapy and medication will be able to reduce the traumaexperienced by Anna Fox.